Integrating Affordable Housing with Transit: Where are the Transit Deserts? - Peng Chen; Jihao Deng (Findings)
This study analyzed transit deserts in Seattle using spatial principal component analysis. We ranked factors related to transit deserts and incorporated the spatial and temporal features of transit services. We found that transit access was the main factor that contributed to transit deserts. We identified clustered and scattered transit deserts. The clustered ones were in dense areas outside of transit corridors, and the scattered ones were located across low-density areas. These findings imply that transit planning and affordable housing should be integrated, and that micro-transit can fulfill the mobility needs of people living in transit deserts.